The search for minerals and creation of first production and territorial complexes in Yamalo-Nenets National District (1932–1937) - A. E. Wolf (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the reasons that stimulated the search for minerals in YamaloNenets Autonomous District in 1933–1937 years and the creation of production and territorial complexes in the mining industry. During this period the district was transferred from one territorial unit to another three times. Yamal was a part of the Ural region (the central city — Sverdlovsk) until 1933, in 1934 – in the Ob-Irtysh region (the central city — Tyumen), in 1935 it was included in the Omsk region (the central city — Omsk). Initially the search of minerals on the territory of Western Siberia was carried out in respect that the Ural-Kuznetsk combine’s needs, which was built in 1929–1932 years. Resources of adjacent territories (North-Eastern Kazakhstan, Ural, Bashkiria, Western Siberia) were used for maintenance of the complex. At that time exploration work was conducted on the whole territory of the Ural region with the exception of the Yamalo-Nenets Autonomous District. After formation of the regional local lore organization in the Ob-Irtysh region (JuneAugust, 1934) and creation of its structural division in the Yamalo-Nenets National District (September-December, 1934), there were data on availability in the district of minerals in mass media. The government has decided that if there are minerals then there should be its own production. In 1935–1936, Yamalo-Nenets District Commitee applied to the Omsk regional Executive Committee for the allocation of funds for the district for the construction of mining industry — brick and limestone industry